Immunogenicity of Quadrivalent Human Papillomavirus Vaccine in Organ Transplant Recipients - Kumar, D. (Am J Transplant, 2013)
Solid organ transplant recipients are at risk of morbidity from human papillomavirus (HPV)-related diseases. Quadrivalent HPV vaccine is recommended for posttransplant patients but there are no data on vaccine immunogenicity. We determined the immunogenicity of HPV vaccine in a cohort of young adult transplant patients. Patients were immunized with three doses of quadrivalent HPV vaccine containing viral types 6, 11, 16 and 18. Immunogenicity was determined by type-specific viral-like protein ELISA. Four weeks after the last dose of vaccine, a vaccine response was seen in 63.2%, 68.4%, 63.2% and 52.6% for HPV 6, 11, 16 and 18, respectively. Factors that led to reduced immunogenicity were vaccination early after transplant (p = 0.019), having a lung transplant (p = 0.007) and having higher tacrolimus levels (p = 0.048). At 12 months, there were significant declines in antibody titer for all HPV types although the number of patients who remained seropositive did not significantly differ. The vaccine was safe and well tolerated. We show suboptimal immunogenicity of HPV vaccine in transplant patients. This is important for counseling patients who choose to receive this vaccine. Further studies are needed to determine an optimal HPV vaccine type and schedule for this population.